Footprints in Time: The Longitudinal Study of Indigenous Children - Key Summary Report from Wave 3 - FaHCSIA, LSIC Data Team (Canberra, ACT, 2012)
Footprints in Time: the Longitudinal Study of Indigenous Children is the most comprehensive source of longitudinal information on early childhood development for Aboriginal and Torres Strait Islander people. It shows how early childhood experiences can impact on later life and provides policy makers with information about ‘what matters’ and ‘what works’ for producing improved Indigenous outcomes.
Footprints in Time The Longitudinal Study of Indigenous Children Key Summary Report from Wave 3
Keywords: Childhood and child development; Childhood and child development